kemampuan literasi sosial MENUMBUHKAN KEMAMPUAN LITERASI SOSIAL SISWA MELALUI PROYEK KOLABORASI ORANG TUA DAN SISWA KELAS V DI SDN 1 WAMEO KOTA BAUBAU - Kosilah, Kosilah; Yurfiah, Yurfiah; Sadepilon, Ferdian; Tiytrianti, Wa Ode Fiona Fika (Jurnal Pengabdian Masyarakat Sabangka, 2025)
This service activity aims to improve the social literacy of grade V students of SDN 1 Wameo, Baubau, through a collaborative student-parent project. Social literacy includes understanding social values, empathy and community participation. Students interviewed parents about life experiences with social values, such as gotong royong, tolerance, hard work and caring. The interview results are processed into a narrative and presented in class. This method trains communication, social understanding, writing, and public speaking skills. As a result, students are better able to identify social values, while parents' participation in learning increases. This activity also strengthens the student-parent emotional connection and creates meaningful contextual learning.